The Effect of Medical Treatment of Attention Deficit Hyperactivity Disorder (ADHD) on Foster Care Caseloads: Evidence from Danish Registry Data. (September 2015) - Fallesen, Peter; Wildeman, Christopher
Since the early 2000s, foster care caseloads have decreased in many wealthy democracies, yet the causes of these declines remain, for the most part, a mystery. This article uses administrative data on all Danish municipalities ( N = 277) and a 10% randomly drawn sample of all Danish children ( N = 157, 938) in the period from 1998 to 2010 to show that increasing medical treatment of attention deficit hyperactivity disorder (ADHD) accounts for a substantial share of the decrease in foster care caseloads. According to our estimates, the decline in foster care caseloads during this period would have been 45% smaller absent increases in medical treatment of ADHD. These findings are especially provocative in light of recent research showing ambiguous effects of medical treatment of ADHD. Future research should be attentive to how medical treatment aimed at addressing children's acute behavioral problems could also have a powerful effect on foster care caseloads.